KARAKTERISASI RESERVOIR KARBONAT MENGGUNAKAN INVERSI IMPEDANSI AKUSTIK BLOK ‘X’, FORMASI TUBAN, CEKUNGAN JAWA TIMUR - Juventa Juventa; Ahmad Fakhri Bobbybuana; Nasri M Z; Fitriyanda Herawan; Ahmad Dzikra Fatahillah (Institut Teknologi Sepuluh Nopember, 2022)
Carbonate reservoirs are usually difficult to map and identify in seismic sections due to their complex structure and diagenetic material with high heterogeneity. The East Java Basin is a perfect example of these complex carbonate structures with excellent hydrocarbon accumulation. In order to obtain a better characterization of the carbonate reservoir in this basin, acoustic impedance inversion is performed in here. Acoustic impedance is a product of seismic P wave velocity and density, where velocity and density are properties commonly used to describe rocks in a reservoir. Based on the sensitivity analysis results, the sensitive parameters to describe the reservoir are acoustic impedance, porosity, sonic, and density. Inversion results showed the range of acoustic impedance values in the Tuban Formation between 23000 – 50000 (ft/s).(g/cc) and porosity transformation results showed a value range of 8 – 22%. Depth structure map, acoustic impedance and porosity section slices showed the distribution pattern of reservoir zones lying in the West - Southwest direction with high structural elevations or located on the top structure reservoir carbonate at a depth of 2500 meters below the surface